Protease na alimentação de frangos de corte - Christiane Fernanda de Queiroz Matias (2012)
This experiment aimed to evaluate the effects of protease (produced by Bacillus licheniformis strain PWD-1) upon metabolization coefficient of nutrients, performance and slaughter yield from male Cobb® broilers, fed diets containing feather meal. Two experiments were conducted with a completely randomized design in 2x2 factorial arrangement - with (0,05%) or without enzyme addition x considering or not nutrient improvement value from protease, with seven replicates per treatment group. In experiment 1 was evaluated the metabolization coefficient of dry matter (MCDM), crude protein (MCCP) and ether extract (MCEE) in initial phase (9-12/d/old) and growth (29-32/d/old). In the initial phase was observed that regardless of enzyme addition broiler chickens fed diet considering nutrient improvement value had higher MCCP (P0.05). However, MCDM and MCEE were not affected (P>0.05). In the growth phase, there were interactions between treatments for the variables MCCP and MCEE. The birds fed diets considering nutrient improvement without enzyme (negative control) showed better results (P 0.05) for MCCP and MCEE. In the treatments with enzyme, the best MCEE (P 0.05) was obtained with the treatment not considering nutrient improvement (over the top). In experiment 2 was evaluated the performance of broilers from 1-38-d-old and the slaughter yield at 38-d-old. In the initial phase weight gain (WG) was greater (P0,05) on birds fed diets not considering nutrient improvement value, regardless of enzyme addition. Feed intake (FI) and viability were not affected (P> 0.05) by treatments. The best results for feed conversion ratio (FCR) (P 0.05) were obtained from chickens fed diets without considering nutrient improvement, regardless of the addition of enzymes. In the growth phase, there was no interaction between the treatments for the performance and slaughter yield. Regardless of enzyme addition, WG and FCR were greater (P0,05) in broilers that received diets not considering nutrient improvement value from protease. Regardless of the nutrient improvement value, the addition of enzyme increased (P 0.05) the WG and FI, there was no effect of enzyme addition on the FCR (P> 0.05). The best carcass yield (P0,05) was obtained (P 0.05) from birds fed diets considering nutrient improvement, regardless of enzyme addition. Treatments did not influence (P>0,05) commercial cuts. The best results for metabolization coefficient of crude protein and ether extract were obtained with birds fed diets without enzyme and considering nutrient improvement value from protease and birds fed diets with enzyme and not considering nutrient improvement value from protease (over the top). Was observed that enzyme addition improved performance, despite had no influence in the cuts yielding of broiler. Moreover, there were evidences that nutrient improvement value from protease seems to be excessive in commercial diets for broilers.